Aktualisasi Self-concept dalam Mewujudkan Tujuan Dakwah (Pendekatan Psikologi Dakwah) - Hasyim Hasanah (Alhadharah: Jurnal Ilmu Dakwah, 2017)
This article discusses the actualisation of self-concept in achieving the goals of dakwah through psychological approach. Dakwah is a process of total Islamisation through a series of activities involving transformation, transmission and diffusion of Islamic values and teachings. Dakwah aims at disseminating, developing, explaining and transmitting Islamic values to the individual in order to achieve happiness. This goal can be achieved by developing the human personality through the actualisation of the self-concept as an important part of the human personality to achieve happiness. Self-concept as a description of a person about himself integrated with the combination of physical, psychological, social, emotional, aspirational, and religious beliefs and accomplishments to be achieved. A person with a positive self-concept will be able to direct themselves optimally to achieve the dakwah objectives, namely salvation and happiness in the world and the hereafter.